Growth and morpho-physiological responses of coffee (Coffea canephora L.) and lanzones (Lansium domesticum Correa) seedlings to waterlogging (The Philippine Journal of Crop Science, 2018)
An experiment was conducted from /march to April 2018 in Los Baños, Laguna to Evaluate the growth and developmental responses to Robusta coffee (Coffea canephora L.) and lanzones (Lansium domesticum Correa) seedlings to waterlogging. To characterize the relative sensitivity of these species to waterlogged conditions, four-month old seedlings were maintained for five weeks under three soil moisture regimes: field capacity (FC); continuous waterlogging (CW); where the medium was kept saturated all throughout; and intermittent waterlogging (IW), where the medium was alternately subjected to three days of continuous waterlogging followed by four days under FC. After 2 weeks in CW, both species exhibited stress symptoms like reduced growth rate (seedling height, stem diameter, and leaf emergence), lower leaf chlorophyll content, leaf necrosis, and leaf abscission. Poor shoot growth of coffee and lanzones seedlings under CW can be linked to poor development of the root system. Because of waterlogging, brownish/grayish, shorter and thinner roots with less ramified branching were produced. This was exacerbated by the disintegration and decay of substantial amount of root peridermal and cortical layers. Our IW results also revealed that coffee is more tolerant to waterlogging stress than lanzones seedlings; coffee grew better that 3-d waterlogging cycles was interspersed with withdrawals of excess water. Leaf abscission in IW commenced 2 weeks later in coffee, with no seedling mortality at the end of 5-week period. The intensity of these stress symptoms was also significantly reduced in lanzones under IW, albeit the onset of leaf abscission and seedling mortality was just the same as CW. recovery of both species from waterlogging stress was attributed to enhanced formation of new roots on pre-existing roots and initiation of lenticel hypertrophy, which translated to better shoot morpho-physiological characteristics.